2008
DOI: 10.1140/epjb/e2008-00073-5
|View full text |Cite
|
Sign up to set email alerts
|

Intra-cellular traffic: bio-molecular motors on filamentary tracks

Abstract: Molecular motors are macromolecular complexes which use some form of input energy to perform mechanical work. The filamentary tracks, on which these motors move, are made of either proteins (e.g., microtubules) or nucleic acids (DNA or RNA). Often, many such motors move simultaneously on the same track and their collective properties have superficial similarities with vehicular traffic on highways. The models we have developed provide "unified" description: in the low-density limit, a model captures the transp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Perhaps the simplest models of active biological transport are those of isolated molecular motors that move along one-dimensional tracks such as actin, microtubules, DNA, or RNA. Motors are enzymes such as dynein, kinesin, and myosin that hydrolyze molecules such as ATP or GTP, turning the free energy released to directed motion along their one-dimensional substrate [272,273]. Motoring is necessary for sustaining cell functions such as mediating cell swimming and motility and intracellular transport of biomolecules, particularly at length scales where diffusion is not efficient, or where spatial specificity is required.…”
Section: Simple Models Of Molecular Motorsmentioning
confidence: 99%
“…Perhaps the simplest models of active biological transport are those of isolated molecular motors that move along one-dimensional tracks such as actin, microtubules, DNA, or RNA. Motors are enzymes such as dynein, kinesin, and myosin that hydrolyze molecules such as ATP or GTP, turning the free energy released to directed motion along their one-dimensional substrate [272,273]. Motoring is necessary for sustaining cell functions such as mediating cell swimming and motility and intracellular transport of biomolecules, particularly at length scales where diffusion is not efficient, or where spatial specificity is required.…”
Section: Simple Models Of Molecular Motorsmentioning
confidence: 99%
“…Mean-field methods have also been extensively used [16], since they are easily tractable and yield a good approximation in many cases. There has been much extension of this simple model, for example variable hopping rates (site or particle dependent) [21,22,23], extended particles which cover more than one site [6,24], branching lattices [25,26], particles which have multiple internal states [27,28,29], as well as a TASEP with a constrained reservoir of particles [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Given the "radial" derivative of the action, given by equation (23), it is straightforward to calculate the imaginary part of the action, which is related to the Hawking temperature through the tunneling probability Γ ∝ e −ImI = e −E/T . While there are a number of techniques which have been introduced for this step [44][45][46][47][48][49][50][51], we will here follow the ideas recently summarized in [52]. In particular, it is found that there are two separate contributions to the imaginary part of the action: one coming from the discontinuity of the time coordinate ∆t, and another coming from a pole, at the horizon, which arises when integrating the radial part of the action.…”
Section: B Tunnelingmentioning
confidence: 99%